2017
DOI: 10.1002/ijc.30673
|View full text |Cite
|
Sign up to set email alerts
|

Identifying high risk individuals for targeted lung cancer screening: Independent validation of the PLCOm2012 risk prediction tool

Abstract: Lung cancer screening with computerised tomography holds promise, but optimising the balance of benefits and harms via selection of a high risk population is critical. PLCO is a logistic regression model based on U.S. data, incorporating sociodemographic and health factors, which predicts 6-year lung cancer risk among ever-smokers, and thus may better predict those who might benefit from screening than criteria based solely on age and smoking history. We aimed to validate the performance of PLCO in predicting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 35 publications
2
65
0
Order By: Relevance
“…13,14 Weber et al applied the PLCO m2012 model to the Australian smokers cohort from the 45 and Up Study and reported that it is applicable and generalisable to the Australian population. Only 23 (10%) participants undergoing CTCA were eligible for screening using the PLCO m2012 risk score and an age range of 55-80 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13,14 Weber et al applied the PLCO m2012 model to the Australian smokers cohort from the 45 and Up Study and reported that it is applicable and generalisable to the Australian population. Only 23 (10%) participants undergoing CTCA were eligible for screening using the PLCO m2012 risk score and an age range of 55-80 years.…”
Section: Discussionmentioning
confidence: 99%
“…13 Participants with a PLoCO m2012 risk of >1.5% were categorised as high risk and those with a risk of <1.5% were categorised as low risk. 13 Participants with a PLoCO m2012 risk of >1.5% were categorised as high risk and those with a risk of <1.5% were categorised as low risk.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In more recent and extensive external validation studies, however, the PLCO M2012 model demonstrated the best performance, with respect to discrimination, calibration, sensitivity, and specificity, although not exceedingly better than the Bach model [45, 46]. In support, a study of >95,000 Australian smokers aged ≥45 years also found that the PLCO M2012 model displayed good calibration and discrimination (AUC, 0.80), and that its performance was largely driven by the main predictors of the Bach model, age and smoking history [47]. …”
Section: Predicting Lung Cancer Risk Prior To Screening Initiationmentioning
confidence: 96%
“…The service was designed to minimise barriers to participation by reducing travel and increasing convenience/service accessibility. We selected screening participants according to individualised risk, using the PLCO M2012 model, at a 6-year lung cancer risk threshold of ≥1.51% 6. A similar approach was used in the UK Lung Cancer Screening Trial (UKLS), which selected participants based on 5-year risk ≥5% (Liverpool Lung Project model), this was cost-effective and resulted in a high prevalence of lung cancer 7…”
Section: Introductionmentioning
confidence: 99%